Review on Tannic Acid: Potensial Sources, Isolation Methods, Aplication and Bibliometric Analysis - Farikha Maharani; Indah Hartati; Vita Paramita (Universitas Muhammadiyah Purwokerto, 2022)
Tannic acid is the simplest form of astringent hydrolysable tannin in which naturally occurring in practically all aerial plant tissues and regarded as the most famous tanning material. Tannic acid having various types of pharmacological activities including anti-viral, anti-cancer, anti-oxidant, anti-microbial, anti-helminthic, anti- haemorrhoids, and anti-diarrhea. Tannic acid can be isolated from various parts of herbaceous and woody plants via different methods such as maceration, soxhletation, micro-channeling and solvent distillation. Tannic acid also found other prospective use in numerous fields such as in textile, leather, corrosion prevention and in rubber based epoxy resin. Bibliometric analysis shows research on tannic acid application trend is move towards the application of tannic in hydrogel formulations and incorporation.